New-Onset Atrial Fibrillation in Critically Ill Patients - Stephanie Sibley; John Muscedere (Canadian Respiratory Journal)
New-onset atrial fibrillation is a common problem in critically ill patients, with reported incidence ranging from 5% to 46%. It is associated with significant morbidity and mortality. The present review summarizes studies investigating new-onset atrial fibrillation conducted in the critical care setting, focusing on the etiology, management of the hemodynamically unstable patient, rate versus rhythm control, ischemic stroke risk and anticoagulation. Recommendations for an approach to management in the intensive care unit are drawn from the results of these studies.